Lunasin: A Novel Cancer Preventive Seed Peptide - Hernández-Ledesma, Blanca (Libertas Academica, 2008)
Cancer is one of the leading causes of deaths in the Western world. Approximately one-third of these deaths are preventable by lifestyle factors, including modification of nutritional habits. Studies have demonstrated that adequate nutrition with certain types of foods containing bioactive compounds might offer significant protection against carcinogenesis. Soybeans contain a variety of phytochemicals with demonstrated anticancer activity, including isoflavones, protease inhibitors, and more recently lunasin, a novel cancer preventive seed peptide. Initially isolated from soybean, lunasin has also been reported in barley and wheat. The purpose of this review is to summarize the most recent evidence on the possible benefits of lunasin for cancer prevention.